(untitled) (Journal of Armed Forces Medical College, Bangladesh, 2019)
Introduction: Colonoscopic biopsy is important in the diagnosis and treatment of suspected colonic diseases as it is a diagnostic procedure of choice for patients with gastrointestinal disorders lasting for several weeks to months. Histomorphological evaluation of colonic biopsy is important for specific diagnosis, for determining the extent of the disease and its response to therapy and for detecting complications. Objective: To evaluate colorectal mucosal lesion by histopathological examination and to confirm the diagnosis of different gastrointestinal diseases including malignancies. Materials and Methods: This descriptive cross-sectional study was conducted on 330 colonoscopic biopsies with different gastrointestinal disorders from January 2014 to December 2016 in the Department of Pathology, Armed Forces Hospital, Kuwait. Results: About 75.2% of cases were male with average age was 45 years with ranging 10-80 years. Out of 330 biopsies specific diagnosis was made in 63% cases and among the specific diagnosis, tubular adenoma was the commonest (21.22%) followed by inflammatory bowel diseases 13.94% cases. Total malignant cases were 7.60% and majority of them in the age group of 41-60 years. Conclusion: The importance of colonoscopic biopsies lies especially in some chronic diarrhoea, alteration of bowel habit and per rectal bleeding. Moreover with the early histopathological diagnosis by detecting the precancerous lesion, like Ulcerative colitis, adenomatous polyp, patient can get rid of developing cancer and thereby saved life. Journal of Armed Forces Medical College Bangladesh Vol.13(2) 2017: 54-58